Gambaran Pengetahuan Perilaku Hidup Bersih dan Sehat pada Lanjut Usia di Desa Lueng Daneun Kecamatan Peusangan Siblah Krueng Kabupaten Bireuen - Zulheri; Maria Ulfa; Fadli Syahputra; Henki Adisa Putra (Public Health Journal, 2026)
The preliminary study conducted by the researcher at the ILP Integrated Health Post (Posyandu) in Lueng Daneun Village, the researcher interviewed ten elderly people, seven out of ten respondents paid less attention to personal hygiene, such as not washing their hands before eating, then consuming less vegetables and fruit every day, then less physical activity in daily life. This study aims to describe the knowledge of Clean and Healthy Living Behavior (PHBS) in the elderly. The quantitative descriptive method uses a cross-sectional approach design. The population and sample were 120 elderly with an age category above 60 years, and the data analysis used was univariate analysis (descriptive analysis). The level of PHBS knowledge of most elderly people is in the less category as much as 62.5%. The data shows that half of the elderly have had at least 3 of the 7 PHBS indicators used in this study. Health promotion programs related to PHBS can be implemented by developing health-oriented development policies, empowering communities, improving family skills regarding PHBS, bringing health services and health education closer so that people can more easily obtain health information.